Comparison Of Bioethanol Production From Corncob And Sugarcane Bagasse On Fermentation Process By Saccharomyces Cerevisiae (Baker’s Yeast) - Toh, Hwee Ting; Nor Faizah Razali; Noor Akhmazillah Mohd Fauzi (Progress in Engineering Application and Technology, 2022)
Bioethanol is a potential alternatives source of energy from renewable materials as compared to non-renewable energy sources from fossil fuels. The purpose of this research is to study the comparison of bioethanol production from corncob and sugarcane bagasse and the effect of pH on the fermentation process by Saccharomyces cerevisiae (baker’s yeast). The methodology of bioethanol production including the pre-treatment of feedstock, media preparation, fermentation process and distillation. For analytical methods, this involves the bioethanol yield produced, standard curve and substrate efficiency. From the result, it can be found out that the pH that will have the highest production of bioethanol is at pH 4.5 at temperature 37℃. Sugarcane bagasse will have a higher bioethanol conversion and better substrate efficiency than corncob. The sugarcane bagasse has a higher cellulose content, which means that the sugar concentration that can be utilized by yeast is higher. As the result, sugarcane bagasse has higher substrate efficiency compared to corncob at 63.98%, 99.06% and 81.59%. For overall substrate efficiency for both feedstocks, the highest efficiency was obtained at pH 4.5, which is 99.06% for sugarcane bagasse and 75.74% for corncob. In bioethanol conversion, sugarcane bagasse has a higher percentage than corncob at 66.82%, 98.65% and 85.23%. In conclusion, sugarcane bagasse is more efficient in bioethanol production while the most suitable pH for S.cerevisiae in bioethanol production is pH 4.5. In the future, more research should be conducted to study the effect of the parameter during the fermentation process by yeast in order to produce a better yield of bioethanol at the highest efficiency.